Epidemiology, diagnosis, and prevention of bovine respiratory disease complex - Hanzlicek, Gregg Alan (Kansas State University, 2010)
The objective of my research was to generate novel information concerning the epidemiology, diagnosis and prevention of bovine respiratory disease complex (BRDC), a common pre-weaning and post-weaning beef calf disease. To reach my objective, I conducted three prospective field trials within post-weaned calf populations, and one retrospective study of pre-weaned calves utilizing survey data. I evaluated differences in behavior, health and performance in calves receiving multiple component health programs. Calves in a minimally invasive program, which included primarily non-injectable products, displayed less aversion to initial product administration but experienced higher BRDC morbidity (P = 0.02) and poorer performance (P = 0.04) compared to calves in a more invasive (all injectable products) program. Secondly, in a study of Mannheimia haemolytica inoculated calves, I found that no parameter included in physical examinations, or common blood component evaluations could discern health from disease. However, disease recognition was aided by the measurement of the number of steps taken by a calf in a 24 hour period. None of the parameters that were evaluated predicted the severity of lung pathology. Thirdly, I conducted a study in post-weaned feeder calves that determined prevalence estimates for Mollicutes in general, and Mycoplasma bovis specifically, and their respective associations with health and performance. Nasal Mollicutes prevalence was high on arrival, and differences in calf performance were associated with (P < 0.01) nasal prevalence. More than half of the calves seroconverted to M. bovis; calves not seroconverting gained more weight (0.49 kg/head/day) during the study than those calves that did seroconvert (0.35 kg/head/day). Finally, I conducted a retrospective analysis of national U. S. cow-calf survey data to identify herd level management practices associated with pre-weaned calf BRDC. I found feeding antibiotics to pre-weaned calves, importing cattle, the number of outside visitors, economic purpose of the cow-calf operation, and breeding management of the herd were associated with herd-level pre-weaning BRDC rates. My research projects generated unique information concerning the epidemiology of important pathogens, differences among preventive health programs, objective BRDC diagnostic parameters, and pre-weaning BRDC risk factors. These research studies reinforce the complexity of BRDC and demonstrate the pathogen, animal and management factors affecting BRDC risk in pre- and post-weaned beef calves.
Keywords: Epidemiology; Bovine respiratory disease; Agriculture, Animal Pathology (0476); Biology, Veterinary Science (0778)